Registration of Ownership Rights Over Customary or Customary Land based on Law No. 5 of 1960 concerning Basic Regulations on Agrarian Principles - Gatot Efrianto (International Journal of Social Service and Research, 2023)
Land is the place where people of customary law communities live, and land also provides livelihood for them. Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA), agrarian law that applies to earth, water, and space is customary law where the joints of the law come from the local customary law community, as long as it does not conflict with national and state interests based on national unity and Indonesian socialism. This research study is normative juridical as the main approach, considering that the discussion is based on laws and legal principles that apply in the issue of customary or customary land registration procedures. Customary land rights are authorities, which according to customary law are owned by customary law communities over certain areas that are the environment of their citizens. This position of authority allows communities to benefit from natural resources, including land, within the area for their survival. The Land Registry is called Recht Cadaster. Conversely, for land rights that are subject to customary law, land registration is not carried out so that it does not produce a certificate, but a proof of payment of tax on land, for example Girik, and even if a land registration is carried out for land rights subject to customary law, this is known as Fiscaal Cadaster. Although customary land is not the object of land registration, based on the provisions of the Minister of Agrarian State/Head of the National Land Agency Number 5 of 1999, Article 4 paragraphs (1) and (2) stipulate that customary land can be controlled by individuals and legal entities by registering as land rights if desired by the right holder, namely citizens of customary law communities according to the provisions of the applicable customary law.